Cities of Kyiv and Sevastopol: especially constitutional-legal status - Магновський, Ігор Йосифович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2010)
Problem questions of constitutional-legal status of cities of Kiev and Sevastopol are considered, their features determined.